TEACHER’S CORRECTIVE FEEDBACK ON STUDENTS’ ORAL RESPONSES - Febrianingrum, Lasmi (Universitas Muhammadiyah Palembang, 2020)
This study investigated oral corrective feedback provided by the teacher and students’ uptake following teacher’s corrective feedback in accelerated class. The researcher explored how the teacher provided corrective feedback during speaking activity and how the high proficiency level students were encouraged to react to it. The observations in several meetings were done with the help of some other instruments like audio video recorder, fieldnote and interview guide. The results show that the teacher preferred to use recast in order not to interrupt the flow of students’ speech and keep students’ mood or feeling. On the contrary, the students preferred to be corrected using other techniques that could make them think more, encourage them to correct the utterances by themselves. Moreover, the results show that students applied repetition and incorporation uptake that let the students construct longer utterance. It can be concluded that there is a gap between teacher’s choice in correcting students’ error and students’ expectation.